Proteomic analysis of the mucus of the photosynthetic sea slug Elysia crispata - Lopes, Diana (2024)
Elysia crispata is a tropical sea slug that can retain intracellular functional chloroplasts from its algae prey, a mechanism termed kleptoplasty. This sea slug, like other gastropods, secretes mucus, a viscous secretion with multiple functions, including lubrication, protection, and locomotion. This study presents the first comprehensive analysis of the mucus proteome of the sea slug E. crispata using gel electrophoresis and HPLC-MS/MS. We identified 306 proteins in the mucus secretions of this animal, despite the limited entries for E. crispata in the Uniprot database. The functional annotation of the mucus proteome using Gene Ontology identified proteins involved in different functions such as hydrolase activity (molecular function), carbohydrate-derived metabolic processes (biological processes) and cytoskeletal organization (cell component). Moreover, a high proportion of proteins with enzymatic activity in the mucus of E. crispata suggests potential biotechnological applications including antimicrobial and antitumor activities. Putative antimicrobial properties are reinforced by the high abundance of hydrolases. This study also identified proteins common in mucus samples from various species, supporting a common mechanism of mucus in protecting cells and tissues while facilitating animal movement. Significance: Marine species are increasingly drawing the interest of researchers for their role in discovering new bioactive compounds. The study "Proteomic Analysis of the Mucus of the Photosynthetic Sea Slug Elysia crispata" is a pioneering effort that uncovers the complex protein content in this fascinating sea slug's mucus. This detailed proteomic study has revealed proteins with potential use in biotechnology, particularly for antimicrobial and antitumor purposes. This research is a first step in exploring the possibilities within the mucus of Elysia crispata, suggesting the potential for new drug discoveries. These findings could be crucial in developing treatments for severe diseases, especially those caused by multidrug-resistant bacteria, and may lead to significant advances in medical research.